DAMPAK NIKAH SIRRI TERHADAP HAK WARIS ANAK DALAM PERSPEKTIF FIQIH DAN HUKUM POSITIF - Mas'ut, Mas'ut (Diponegoro Private Law Review, 2018)
Marriage is an institution that unites between a man with a woman to be husband and wife in fostering and forming a family sakinah mawaddah and rahmah There are still many people who make marriages that are not in accordance with the pillars and conditions of marriage in accordance with religious teachings. And so there is a marriage that is in accordance with the pillars and religious requirements, but not registered in the Officer of Marriage Certificate in the Office of Religious Affairs. Such marriages are commonly called marriage sirri or marriage under the hands. The marriage of sirah will result in the law of the born child, which is not subject to legal protection of the rights of the child, including the right to obtain inheritance from his real father. However, if viewed with the glass eyes jurisprudence children born are considered to still get his rights from his father, including can inherit his father's property. Keyword : The Marriage of Sirri,Inheritance Rights